The impact of islet mass, number of transplants, and time between transplants on graft function in a national islet transplant program. Issue 1 (22nd August 2021) - Forbes, Shareen; Flatt, Anneliese J.; Bennett, Denise; Crookston, Robert; Pimkova, Mirka; Birtles, Linda; Pernet, Andrew; Wood, Ruth C.; Burling, Keith; Barker, Peter; Counter, Claire; Lumb, Alistair; et al.
Abstract : The UK islet allotransplant program is nationally funded to deliver one or two transplants over 12 months to individuals with type 1 diabetes and recurrent severe hypoglycemia. Analyses were undertaken 10 years after program inception to evaluate associations between transplanted mass; single versus two transplants; time between two transplants and graft survival (stimulated C‐peptide >50 pmol/L) and function. In total, 84 islet transplant recipients were studied. Uninterrupted graft survival over 12 months was attained in 23 (68%) single and 47 (94%) ( p  = .002) two transplant recipients (separated by [median (IQR)] 6 (3–8) months). 64% recipients of one or two transplants with uninterrupted function at 12 months sustained graft function at 6 years. Total transplanted mass was associated with Mixed Meal Tolerance Test stimulated C‐peptide at 12 months ( p  < .01). Despite 1.9‐fold greater transplanted mass in recipients of two versus one islet infusion (12 218 [9291–15 417] vs. 6442 [5156–7639] IEQ/kg; p  < .0001), stimulated C‐peptide was not significantly higher. Shorter time between transplants was associated with greater insulin dose reduction at 12 months (beta −0.35; p  = .02). Graft survival over the first 12 months was greater in recipients of two versus one islet transplant in the UK program, although function at 1 and 6 years was comparable. Minimizing the interval between 2 islet infusions may maximize cumulative impact on graft function. Abstract : Data from the UK Islet Transplant Consortium demonstrate comparable 1‐year graft function and 6‐year graft survival in recipients of 2 versus 1 islet allotransplant but attenuated graft outcomes when the 2nd transplant is more than 6 months after the 1st, leading to allocation policy changes to facilitate a 2nd allotransplant within 3 months of the 1st.